Wideband planar dipole based on dual‐layer artificial magnetic conductor. Issue 19 (15th July 2019) - Shi, Suyang; Yang, Peigang; Zhou, Lei; Chen, Wenjun
Abstract : A wideband planar dipole based on dual‐layer artificial magnetic conductor (AMC) is designed. First, the size of dual‐layer AMC is reduced by more than half, and the in‐phase band is wider than the single‐layer AMC. Then, the improvement of large scan angle can be obtained by the offset between two layers of AMC in two directions. At last, a wideband planar dipole with 24.5% bandwidth is achieved.